Characteristics associated with anti-HCV serological markers in prisoners in the state of Parana, Brazil: a case-control study - Pazin Marques Silva, Tania Maria; Defante Ferreto, Lirane Elize; Caovilla Follador, Franciele Ani; Vieira, Ana Paula; Yamada, Roberto Shigueyasu; Lucio, Leia Carolina; Titon, Joana Perotta; Torres, Renata Himovski; Amaral, Greicy Cezar do; Coelho, Harnoldo Colares [UNESP] (Elsevier B.V., 2019)
Background: The prison system in Parana, Brazil, is experiencing serious problems related to the increasing number of prisoners. Control of hepatitis C virus (HCV) has become more intense because the incarcerated population is considered a high-risk group for contagious diseases due to the favorable conditions found in prisons for the spread of these morbidities. The objective of this study was to identify features associated with hepatitis C infection among male prisoners in correctional institutions of Parana state, Brazil. Methods: This was a case-control study (27 cases and 54 controls) of men incarcerated in 11 penitentiaries in Parana, Brazil. Information was obtained through a questionnaire in a cross-sectional epidemiological survey on HCV infection during the period from May 2015 to December 2016. Eligible men were recruited after testing positive for anti-HCV antibodies. Cases and controls were selected based on serological results of enzyme-linked immunosorbent assays and were matched by age, location of the penitentiary, and time in prison. Logistic regression analysis was used to identify risk factors for HCV seropositivity. Results: The main significant independent risk factor for the acquisition of HCV infection was the use of injectable drugs (OR=4.00; 95%CI:1.41-11.35; p < 0.001). Conclusions: This study provides evidence that HCV infection is associated with drug use by this population. This information is pivotal for tailoring prevention programs and guiding specific socioeducational measures that aim to reduce or prevent HCV transmission within the prison setting. (C) 2019 Sociedade Brasileira de Infectologia. Published by Elsevier Espana, S.L.U.
Keywords: Hepatitis C; Risk factors; Prisoners